Simulation on Water Behavior in a Retention Pond at UNITEN - Zahari N.M.; Amieroul Mirza Mohamad M.; Zawawi M.H.; Abas A.; Aziz N.A.; Nurhikmah F. (IOP Publishing Ltd, 2023)
Retention pond have been used widely to manage stormwater runoff to avoid flooding and downstream erosion and even improve water quality. It is an artificial pond that have vegetation around the perimeter and a permanent pool of water. This paper presents the study on water flow behaviours in UNITEN's retention pond by using ANSYS Fluent. Findings shows that the velocity of water in wet condition is higher than the dry condition because of an additional inlet in wet condition to imitate the heavy rainfall phenomenon. It is also found that the water pressure in wet condition is higher compare to dry condition. Therefore, the conditions that have a higher movement of water can be determined through this simulation. Based on the findings, it can be concluded that the wet condition have a high movement of water behaviour compare to dry condition. Published under licence by IOP Publishing Ltd.